Ethical oversight of multinational collaborative research: lessons from Africa for building capacity and for policy (2007)
Researchers and others involved in the research enterprise from 12 African countries met with those working in ethics and oversight in the United States as part of an effort to develop research ethics capacity. Drawing on a wealth of experience among participants, discussions at the meeting revealed five categories of issues that, warrant careful attention by those engaged in similar efforts as well as international policymakers and those charged with oversight of research. (1) Principal investigators should build 'true research teams' where members of the team are meaningfully involved in decisions regarding the protocol and its implementation. (2)There should be explicit discussion about the 'standard of care' at the outset of project planning that includes clarification of the terminology that is being used. (3) While internationally collaborative research may involve populations that have inherent vulnerabilities, it is important to recognize the limitations of host country solutions (such as elaborated consent processes) and look for means to negotiate appropriate protections for those willing to participate. (4) In conducting research involving biological materials it would be prudent to develop 'material transfer agreements at the outset of the study to clarify expectations and to minimize the likelihood of harm. (5) Those engaged in internationally collaborative research need to be alert to the potential conflicts of interests of host country ethics committees during the approval process and to take measures to manage them if they indeed exist.